Sosialisasi Penggunaan QRIS Sebagai Alat Pembayaran pada UMKM Mie Ayam Mama Elz - Anisa Ratna Sari; Aishwarya Shafa Zahirah; Nonny Laurencia Nawangsari; Erminah Dwi Ambarwati; Mohamad Aziz (P3M Politeknik Negeri Malang, 2023)
The community service program in the form of socialization is carried out in collaboration with the Owner of UMKM Mie Ayam Mama Elz, Katemas, Kudu, Jombang. This activity is motivated by the rapid development of payment instruments which has made the buying and selling process undergo many changes, one of which is payment using QRIS. This activity was carried out with the aim of providing socialization to UMKM Mie Ayam Mama Elz regarding the use of QRIS as an electronic payment instrument that can help and speed up the payment process. The method used is to hold socialization via Google Meet to UMKM Mie Ayam Mama Elz. The results of this activity add to the understanding of UMKM Mie Ayam Mama Elz owners regarding QRIS.